Storage stability of soluble pigments, chlorophylls, and carotenoids in electron‐beam‐irradiated edible lavers (Porphyra umbilicalis) with impact on microbial safety and sensory characteristics. (25th February 2019) - Lee, Eun‐Jin; Ramakrishnan, Sudha Rani; Kim, Gui‐Ran; Kwon, Joong‐Ho
Abstract: BACKGROUND: In this study, we investigated whether electron beam (e‐beam) irradiation can inactivate microbial populations, including aerobic bacteria plate count, fungi, and coliforms, in two types of lavers (dried and roasted). The impact of e‐beam doses of 4 and 7 kGy on microbial populations, color values, total soluble pigments, chlorophylls, and carotenoid content immediately and after storage at 4, 15, 25, and 35 °C for 4, 8, and 12 weeks was also evaluated. RESULTS: The initial microbial load of approximately 10 6 and 10 5  CFU g −1 in both dried and roasted lavers was reduced to 10 4 and 10 1  CFU g −1, respectively, after irradiation at 7 kGy. No further proliferation was observed in irradiated dried lavers during 4 weeks of storage at 4 and 15 °C. When stored at low temperature, the shelf‐life was extended for up to 12 weeks in 7 kGy irradiated dried and roasted lavers. High amounts of soluble pigments and carotenoids were observed during storage in the 7 kGy irradiated dried laver samples at the end of 12 weeks irrespective of temperature. Although the chlorophyll content decreased under the storage conditions, it was comparatively stable in the 7 kGy‐irradiated dried laver. Maximum degradation of color was observed in laver samples subjected to the roasting process. CONCLUSION: Overall, this study indicated that e‐beam irradiation of laver at 7 kGy maintains microbial safety as well as quality attributes during storage for up to 12 weeks. Further, dried laver had more essential compounds than roasted laver. © 2019 Society of Chemical Industry